Rapid Green Synthesis of Ag-TiO2 Nanocomposites via Microwave Irradiation for Water Treatment : Dual Action on Dyes and Bacteria - Devagi, Kanakaraju; D. N., JOSEPH; Y. C., Lim; Micky, Vincent (Asian Publication Corporation, 2025)
The widespread use of hazardous chemicals in traditional methods for synthesizing silver-doped titanium dioxide (Ag-TiO2) nanocomposites poses significant environmental and health concerns, contradicting the goal of sustainable photocatalytic water purification. This study aims to develop a microwave-assisted green synthesis method using plant waste-based material, Allium cepa (onion) peel extract, a readilyavailable material, to deposit silver onto TiO2 with the goal of enhancing its photocatalytic and antibacterial properties. The prepared Ag-TiO2 nanocomposite was applied to remove single and mixed dyes. Characterization techniques confirmed the formation of stable Ag-TiO2 nanocomposite with an average size of 7.36 ± 2.01 nm evenly deposited onto TiO2, resulting in improved responsiveness in the visible light region. UVVis diffuse reflectance spectroscopy and photoluminescence analysis indicated a reduction in the band gap for Ag-TiO2 nanocomposite. The green-synthesized Ag-TiO2 nanocomposite exhibits exceptional photocatalytic efficiency in degrading both cationic dyes and anionic Congo red and methylene blue dyes with a degradation rate of 99.4% and 99.6% individually under UV irradiation. In a mixed dyesolution, the degradation of rhodamine B and methyl orange dyes was significantly accelerated due to the selective interaction of the AgTiO2 nanocomposite with anionic dyes. The green synthesized Ag-TiO2 nanocomposite also showed effective antibacterial properties against Gram-positive bacteria, E. coli and Gram-negative bacteria, S. aureus. This study stresses the capability of green synthesis to generate environmentally benign and high-performing photocatalysts for water treatment applications, effectively degrading contaminants and eradicating undesirable waterborne pathogens.